2021
DOI: 10.1021/acs.langmuir.1c00763
|View full text |Cite
|
Sign up to set email alerts
|

Solution Chemistry to Control Boron-Containing Monolayers on Silicon: Reactions of Boric Acid and 4-Fluorophenylboronic Acid with H- and Cl-terminated Si(100)

Abstract: The reactions of boric acid and 4-fluorophenylboronic acid with H- and Cl-terminated Si(100) surfaces in solution were investigated. X-ray photoelectron spectroscopy (XPS) studies reveal that both molecules react preferentially with Cl–Si(100) and not with H–Si(100) at identical conditions. On Cl–Si(100), the reactions introduce boron onto the surface, forming a Si–O–B structure. The quantification of boron surface coverage demonstrates that the 4-fluorophenylboronic acid leads to ∼2.8 times higher boron cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Therefore, it confirms the neutralization of SiO 2 –H 3 BO 3 –HDTMS hydrogels by NaOH. The core level Si 2p spectra in Figure d showed that a strong peak at 103.36 eV can be assigned to Si–O x species, whereas the weak peak at 102.01 eV is related to the Si–O–B bond, derived from the cross-linking reaction between SiO 2 and prehydrolyzed HDTMS and H 3 BO 3 . All the analyses indicated that the neutralized SiO 2 –H 3 BO 3 –HDTMS hydrogel had been well synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it confirms the neutralization of SiO 2 –H 3 BO 3 –HDTMS hydrogels by NaOH. The core level Si 2p spectra in Figure d showed that a strong peak at 103.36 eV can be assigned to Si–O x species, whereas the weak peak at 102.01 eV is related to the Si–O–B bond, derived from the cross-linking reaction between SiO 2 and prehydrolyzed HDTMS and H 3 BO 3 . All the analyses indicated that the neutralized SiO 2 –H 3 BO 3 –HDTMS hydrogel had been well synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the elemental ratios of P 2p and O 1s decrease with the addition of low-concentration APB, while the percentage of P 2s/B 1s increases, signifying a relative decrease in PSP deposition with APB deposition (Table S1). The shape of the peak then begins to broaden to 192 eV, as seen in Figure h, potentially from the deposition of boron oxides and borates. The ratio of P 2s/B 1s continues to increase with no significant change in the P 2p and O 1s ratios as well as an increase in N 1s compared to the 1% APB coating (as the APB concentration increases), denoting the successful deposition of APB within the coating. Elemental analysis via an electron microprobe confirms the presence of boron, showing a distinct peak form in the area where boron is detected, with increasing concentration compared to the control sample (Figure i).…”
Section: Resultsmentioning
confidence: 95%
“…The comparatively superior stability of Br and I passivation layers enables the use of halogen-passivated Si in real-world processes such as recent work where UHV-prepared Br-Si was transported off-site for solvothermal reactions with hydrazine [36]. Additionally, the ability to prepare ambient stable H and halogen resists opens up the opportunity to integrate APAM feature sizes with selective area chemistries, such as boron-based monolayer doping, that cannot be performed in UHV [44]. Incorporation of advanced and selective chemistries [44][45][46][47] targeting H and halogen passivation layers will be the next step to utilization of atomic precision patterning toward building advanced devices and architectures.…”
Section: Discussionmentioning
confidence: 99%